Study of environment based condition of electromagnetic interference during ECG acquisition - Wong, W. Y. (IEEE, 2012)
The electrocardiograph signal or known as ECG signal is an electrical signal that generated naturally from our heart beat. The signal is commonly used for diagnosis or examining the heart disease. The ECG signal is easily disturb by the Electromagnetic Interference (EMI) of the environment. It is the most headache problem of the advance ECG system. The EMI will affect the patient heart beat data and cause the inappropriate treatment decision made by the doctor. This small error may cause the death of the patient. The study mainly focused to determine the environment in the surrounding that provides the most EMI. Experiment to determine the effect of EMI was done at several places using a portable ECG circuit. The circuit used a 9 V battery as the power supply for ease of mobility to record the ECG signals. Analysis was done to the ECG data that have been taken from different environment. Different environment provide different EMI effect to the ECG signal. The environment of lab that consists of many electronic devices will emitted EMI which will give noise to ECG signal. However, the noise did not affect the ECG patient data. Nevertheless, the EMI emitted by mobile phone is seriously affecting the ECG patient data. From the study, analysis has shown that the more advance and expensive mobile phone, the lesser EMI affected the ECG data.